Analysis of Response Needs for the Development of Animation Video Learning Media on Dynamic Fluid Materials - Veby Penyustia (IJOEM: Indonesian Journal of E-learning and Multimedia, 2023)
This study aims to determine the needs response analysis for the development of animated video learning media for students and teachers. The research was conducted at MAN 1 Bengkulu City, MAN 2 Bengkulu City, and SMAN 10 Bengkulu City in September 2022 with a sample size of 97 students in class XI IPA and 3 physics teachers. The instruments used in this study were observation, interviews and questionnaires, with a descriptive research method using the ADDIE R&D model. Data collection techniques and data analysis used were observation, interviews, and questionnaires. Based on the results of the validity and reliability tests, it was found that the questionnaire required each statement item to be valid and reliable. The results of data analysis stated that students and teachers strongly agreed to develop animated video learning media on dynamic fluid material with a percentage of 81.31 % strongly agree category.